Analisis performa borneo fc di liga sepak bola indonesia: sebuah kajian longitudinal - Iknasius Lagu; Agusti Mardikaningsih; Winarno; Hari Pamungkas; Sudari; Ashari Husen (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
This research aims to analyze the development of Borneo FC performance in the 2023-2024 Indonesian League 1 season. Using the longitudinal method, the data analyzed includes match statistics, standings, goals scored and goals conceded. The results showed that Borneo FC accumulated 70 points, making it  team with the 3rd most points in League 1 this season. They averaged 2.06 points per game, scored 53 goals, making them the second highest scoring team in League 1. The average goals scored per game reached 1.56, showing the sharpness of team's front line. Only 31 goals conceded, making it the lowest conceding team in League 1. The ratio of goals scored and conceded (0.65). The correlation (R) is 0.558from the output obtained the coefficient of determination (R Square) of 0.312, where the effect of goals on points is 31.2%. Tactical changes, coaching changes, and effective management contributed to the team's improved performance. In addition, club's stable financial health and strategic transfer policy supported club's growth. Based on these findings, recommendations for infrastructure improvements, youth development, better financial management, and long-term strategies are suggested to ensure Borneo FC continued success. This analysis provides valuable insights for club management, coaches, and other stakeholders in future strategic decision-making.